The effect of hydro cooling time, storage temperature and storage duration on Saba Banana - Jagathiswarri SupramaniamJagathiswarri Supramaniam (2016)
This study was conducted in Postharvest Lab of Faculty Sustainable Agriculture. The objective of this study was to determine the effect of hydro cooling time, storage temperature and storage duration on Saba banana. The hypothesis that has been tested in this experiment was there is significant difference in the effect of hydro cooling time (CT), storage temperature (ST) and storage duration (SO) on Saba banana. The treatments used in this experiment were different hydro cooling times (0, 112, 7/8); then Saba banana was stored at cold temperature (13±2°C), room temperature (26±2°C) and outside temperature (30±2°C) after hydro cooling for 3 weeks duration. The parameters that have been recorded in this study were weight loss, pulp firmness, skin colour, visual appearance, pH, total soluble solid and titratable acidity. The experimental design that was used for this study was Completely Randomised Design (CRD) with a factorial arrangement of treatments (3eT x 3ST x 4 SO), with three replications and two fruits per treatment per replication. The results were analysed using SAS Version 9.1. Analysis of variance (AN OVA) was used to get the variance among the treatments, storage temperatures and storage duration. LSO was performed to determine difference on the mean values. The results indicate that the cooling time has significantly affected the weight loss, pulp firmness, skin colour L *, skin colour C*, pH, total soluble solid and titratable acidity but it did not affect significantly on skin colour hO and visual appearance. Meanwhile the storage temperature affects significantly all the parameter except skin colour hO and all the parameters have significantly affected at all storage durations. Treatment combinations of cooling time and storage temperature were found to have significant interaction effects on visual appearance and titratable acidity only. The treatment combinations between cooling time and storage duration were found to have significant effect on weight loss, total soluble solid and titratable acidity. The treatment combination between storage temperature and storage duration were found to have significant effects on all the postharvest qualities except for the pH. The treatment combinations between cooling time, storage temperature and storage duration were found to have significant effect on skin colour L *, skin colour C*, visual appearance and titratable acidity. In conclusion, there is no any precooling time that can be suggested for the farmers to be used in their farm because precooling increases the weight loss and reduces visual appearance.